Faktor Internal: Faktor Individual dalam Pengembangan Organisasi di SD IT Madani Islamic School 3 Padang, Kota Padang - Hanifiyah Zahra; Rusdinal, Rusdinal; Hade Afriansyah (Jurnal Ilmu Manajemen dan Pendidikan | E-ISSN : 3062-7788, 2025)
An organization needs to continuously change to stay abreast of dynamic, complex, and sometimes unpredictable environmental developments. School organizational development is an important form of change, but its success is influenced by various factors, including internal factors in the form of individual factors. These individual factors are closely related to each member in the organization. This study aims to analyze individual factors in organizational development at SD IT Madani Islamic School 3 Padang, focusing on relationships between members, cooperation, and financial factors, and reviewing their suitability with existing basic concepts. The study used a descriptive qualitative approach through observation and interviews. The results showed that individual factors have an influence in supporting organizational development, where harmonious relationships between members, good cooperation, and employee financial stability enable program implementation to run smoothly and effectively. These findings confirm that management's attention to interpersonal aspects and employee conditions is key to the success of school organizational development.